PENERAPAN PEMANFAATAN MULTIMEDIA PADA APLIKASI PHOTOMATH DALAM PEMBELAJARAN TRIGONOMETRI KELAS XI MIPA V DI SMAN 3 CILEGON - Amelia Muslimah; Cahyani Ramadannia; Anita Fitri; Finda Dzakiroh; Jaka Wijaya Kusuma (Nindikayla Institute, 2023)
The more advanced technology in the world, the more useful it is.one of them is in global education Where at this time our situation is not yet conducive to the implementation of the learning process. Technology has many benefits in helping solve mathematical problems. The purpose of this study means to find out how to use the application of multimedia photomath applications on triginometric material. The subject we chose was several students of XI MIPA V SMAN 3 CILEGON. In this study we use qualitative methods where this method means research that is descriptive and tends to use analysis. The results of the research we conducted provide results that the photomath application helps most students, but also has negative impacts such as lazy thinking and only relying on photomath in solving math problems without calculating manually. Photomath applications can also have a positive impact, namely students are able to find out the answers to the math problems given